2020
DOI: 10.1111/jir.12714
|View full text |Cite
|
Sign up to set email alerts
|

Physiological arousal and observed behaviour in parent–child interactions involving young children with Down syndrome

Abstract: Background Parents of children with Down syndrome (DS) play an important role in their child's development. Physiological measures, such as electrodermal activity (EDA), can shed light on parent-child relations beyond the behavioural level.The goals of the current study were to assess the feasibility of collecting EDA data in preschool age children with DS, examine the association between parent and child EDA during play-based interactions, and investigate the relation between parent and child EDA and observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…To address potential concerns in our participants, we will thoroughly explain what the wristband is and is not capable of and coach the participants in informing others about their new accessory. The E4 wristband has been used to monitor arousal in 15 children as young as 2 years with Down syndrome during 7-minute parent-child interaction sessions [ 15 ]. EDA data from children were deemed useable (90% of interactions tracked) for 27 out of 30 interactions; from parents, EDA data were useable for 23 out of 30 interactions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address potential concerns in our participants, we will thoroughly explain what the wristband is and is not capable of and coach the participants in informing others about their new accessory. The E4 wristband has been used to monitor arousal in 15 children as young as 2 years with Down syndrome during 7-minute parent-child interaction sessions [ 15 ]. EDA data from children were deemed useable (90% of interactions tracked) for 27 out of 30 interactions; from parents, EDA data were useable for 23 out of 30 interactions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that ML models using 3 minutes of physiological data from a wearable biosensor worn by 20 youths could predict aggressive behaviors in youths with autism spectrum disorders 1 minute prior to their occurrence with relatively high accuracy [ 14 ]. Another study linked behavioral synchrony between 15 fathers and their 2-5–year-old children with Down syndrome to synchrony in the dyads’ electrodermal activity (EDA) measured with wearable biosensors during a play session [ 15 ]. Using speech features as input, ML models have classified the severity of depression [ 16 ] and differentiated between children with and without internalizing disorders [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nine participants had an OCD diagnosis (patients) and 9 youths presented without a psychiatric diagnosis (controls). Other studies have predicted aggressive behavior from wearables worn by 20 youths in 87 hours (10 consecutive days) or behavioral synchrony between father and their child with Down syndrome from wearables worn by 12 families in a 7-minute free play [ 22 , 23 ]. Although the number of participants is low, we followed each participant for 8 weeks, and we argue it will be enough for a feasibility study of prediction possibilities (as a minimum within individuals).…”
Section: Methodsmentioning
confidence: 99%
“…A unique form of data, gathered via electrodermal activity (EDA) from both parents and young children with Down syndrome, was contributed by Lorang et al . (2020) in their paper, Physiological arousal and observed behaviour in parent–child interactions involving young children with Down syndrome . The research was conducted during home visits, during parent–child free‐play sessions, with children who ranged in age from 2 to 5 years.…”
Section: Guide To Papers In This Special Issuementioning
confidence: 99%